2017
DOI: 10.1101/cshperspect.a022236
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Immune Response by TGF-β: From Conception to Autoimmunity and Infection

Abstract: Transforming growth factor b (TGF-b) is a pleiotropic cytokine involved in both suppressive and inflammatory immune responses. After 30 years of intense study, we have only begun to elucidate how TGF-b alters immunity under various conditions. Under steady-state conditions, TGF-b regulates thymic T-cell selection and maintains homeostasis of the naïve T-cell pool. TGF-b inhibits cytotoxic T lymphocyte (CTL), Th1-, and Th2-cell differentiation while promoting peripheral ( p)Treg-, Th17-, Th9-, and Tfh-cell gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
337
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 478 publications
(344 citation statements)
references
References 381 publications
(358 reference statements)
5
337
0
2
Order By: Relevance
“…Immunosuppressive roles of GARP through the regulation of TGF-β As described in the earlier section, TGF-β regulates the differentiation and function of multiple types of immune cells, which in turn inhibits immune responses [56]. Among them, TGF-β plays a central role in conversion of naïve T cells into Tregs.…”
Section: Garp Anchors the Latent Tgf-β Complex On The Cell Surfacementioning
confidence: 96%
See 1 more Smart Citation
“…Immunosuppressive roles of GARP through the regulation of TGF-β As described in the earlier section, TGF-β regulates the differentiation and function of multiple types of immune cells, which in turn inhibits immune responses [56]. Among them, TGF-β plays a central role in conversion of naïve T cells into Tregs.…”
Section: Garp Anchors the Latent Tgf-β Complex On The Cell Surfacementioning
confidence: 96%
“…TGF-β functions as a potent immunosuppressive cytokine [53][54][55][56] and therefore, inhibition of TGF-β signaling in the immune system may lead to an enhancement of tumor immunity. TGF-β suppresses the proliferation of T and B cells and the functions of cytotoxic CD8 + T cells and helper CD4…”
Section: Immune Responsesmentioning
confidence: 99%
“…Transforming growth factor type‐ β (TGF‐β) has many biological activities, and is thought to be a particularly important contributor to fibrosis, angiogenesis, and tissue repair. In addition, TGF‐β can influence T cells, including Th17 and Treg cells (reviewed in), as well as B cells, dendritic cells, NK cells, neutrophils, eosinophils, and MCs (reviewed in ).…”
Section: Mast Cell‐derived Cytokines Growth Factors and Mitogensmentioning
confidence: 99%
“…Immunotherapy based on checkpoint inhibitors and chimeric antigen receptor (CAR) T cells represents a breakthrough in cancer therapy [77]. Mounting evidence indicates that TGF-β is a potent immunosuppressive cytokine involved in suppressive immune responses [9,[78][79][80]. In addition, it has been reported that high levels of TGF-β are frequently found in colorectal carcinomas, which are clinically associated with poor survival in patients [81,82].…”
Section: Rewiring Of Tgf-β Signaling Toward Clinical Applicationsmentioning
confidence: 99%